PERANAN PERAWAT GIGI PUSKESMAS DALAM PERAWATAN GIGI SUSU UNTUK MENINGKATKAN TUMBUH KEMBANG ANAK - MANGINAR SIDABUTAR; FRISKA D. SIMAMORA; MELKISEDEK O. NUBATONIS (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2016)
The physical and mental growth of a child is affected by the health of his teeth and mouth. A child with untreated dental caries can cause recurrent infections, bacteremia, mastication, and sleeplessness and can, in turn, interfere with child growth. This study aims to evaluate the implementation of early childhood caries promotion and prevention programs at Community Health Centers conducted by Dental Nurses managing community dental programs. The results showed that none of the respondents who conducted the program of promotion and prevention of caries in Posyandu on a regular basis and only 33 percent of respondents who undertook early promotional programs and prevention of early caries in infants incidentally. Parents of Infants and Teachers are not involved in early childhood caries promotion and prevention programs conducted by P. None of the referrals from early childhood/family visit to Puskesmas for advanced dental care. Toddler visits to Dental Police Puskesmas are dominated by Toddlers with cases of periodontal abscess and pulpitis. The conclusion of this research is Dental Nurses Dental health program managers do not have a program of promotion and early dental caries in Toddler. Public Health Service, Puskesmas and especially Dental Nurses Puskesmas managing dental health program community need to make and implement a program of promotion and prevention of early caries at baby at Posyandu and toddler in Posyandu, PAUD / TK involving parents and teachers.